EMPLOYER IMAGE FORMATION DURING RECRUITMENT : Perceptions of young professionals in knowledge-intensive services - Miettinen, Lotta (My University, 2020)
Organizations are in a war for talent, as changing demographics, globalization and increasing workforce mobility are decreasing the supply of talented young professionals. This intensifying competition over job applicants has driven organizations to develop ways to differentiate and increase their attractiveness. One way to do this is through development of positive employer image. Recruitment process has been identified as a major determinant of applicants’ employer images. Recruitment process does not anymore only stand for an opportunity for the employer to evaluate applicants, but also as an opportunity for applicants to critically evaluate the employer. Therefore, this study was taken to extend the previous research on how employer image is formed during recruitment process and clarify what can actually be done to contribute to formation of favorable employer image by examining how applicants interpret, value and perceive different cues they receive during the process. In fulfilling the study purpose, recruitment and employer image literatures were merged and as a result the interest was centralized in detecting what specifically is the role of communication, applicant’s personal experience on individual recruitment activities as well as symbolic and instrumental attributes in this equation. Qualitative interviews were conducted to study the phenomena in the eyes of job applicants. The empirical research identified that employer image develops according to different characteristics of recruitment process which taken together forms a holistic employer image. More precisely it was found that during variety of recruitment activities individuals receive messages that contain attributes based on which applicants make conclusions about the employer. Taking a closer look, the evidence highlighted the role of current employees as employer image ambassadors. Additionally, communication evolving around recruitment was identified as a central determinant of employer image. Furthermore, based on the findings, organizations are encouraged to explore and promote symbolic attributes such as atmosphere while seeking differentiation. Taken together, organizations can design and implement interventions in each phase of recruitment to contribute towards formation of clear and favorable employer image. This study was performed in the context of KIBS industry and the empirical evidence was collected by observing perceptions of recent or soon to be graduates. For future research it is recommendable to widen the research context.

Työmarkkinoilla yrityksiä haastaa koventunut kilpailu työvoimasta, jota kiihdyttää väestön ikääntyminen, globalisaatio ja kasvava työvoiman liikkuminen. Voimistuva kilpailu nuorista lahjakkaista työnhakijoista on ajanut yritykset kehittämään keinoja erottuakseen kilpailijoista ja lisätäkseen houkuttelevuutta. Yritykset voivat vastata nykypäivän rekrytoinnin haasteisiin työnantajamielikuvan kehittämisen kautta. Rekrytointiprosessi onkin tunnistettu mahdollisuudeksi muokata työnhakijoiden työnantajamielikuvia yrityksestä. Nykypäivänä rekrytointiprosessi ei ainoastaan toimi yrityksille mahdollisuutena arvioida työnhakijoita, vaan myös mahdollisuutena työnhakijoille arvioida kriittisesti työnantajia. Tässä tutkimuksessa pyritäänkin lisäämään tietoa siitä, kuinka työnantajamielikuva muodostuu rekrytointiprosessissa ja mitä yritykset voivat käytännössä tehdä edistääkseen mielekkään työnantajamielikuvan kehittymistä. Tätä varten analysoidaan ja kuvataan sitä, kuinka työnhakijat tarkastelevat, tulkitsevat ja arvioivat eri signaaleja, joita he saavat rekrytointiprosessin aikana. Tutkimuksen tavoitteiden mukaisesti rekrytointi- sekä työnantajamielikuvakirjallisuudet yhdistettiin. Alustavien löydösten mukaan mielenkiinto kohdistettiin tutkimaan kommunikaation, yksittäisten rekrytointitoimenpiteiden sekä symbolisten ja instrumentaalistien piirteiden roolia työnantajamielikuvan rakentumisessa. Empiirinen aineisto kerättiin laadullisilla yksilöhaastatteluilla, jotta tutkittavaa ilmiötä pystyttiin tarkasteleman työnhakijoiden näkökulmasta. Tutkimuksessa havaittiin, että työnantajamielikuva rakentuu kokonaisarviosta rekrytoinnissa käytetyistä toimenpiteistä ja piirteistä. Eri rekrytointitoimenpiteiden aikana hakija saa tietoa, joka sisältää viitteitä eri piirteistä, minkä perusteella hakija tekee johtopäätöksiä työnantajasta. Tutkimustulokset korostavat erityisesti nykyisten työntekijöiden roolia työnantajamielikuvan muodostumisessa sekä kommunikaation merkittävää vaikutusta tässä yhtälössä. Tutkimustuloksiin perustuen yrityksiä kannustetaan tuomaan esille erityisesti symbolisia, aineettomia piirteitä kuten hyvää työilmapiiriä, tavoitellessaan erottumista kilpailijoista. Yritykset voivat suunnitella ja implementoida keinoja jokaisessa rekrytoinnin vaiheessa edistääkseen selkeän ja mielekkään työnantajamielikuvan muodostumista. Tämä tutkimus toteutettiin tietointensiivisen toimialan kontekstissa ja aineistoa kerättiin vastavalmistuneilta ja pian valmistuvilta työnhakijoilta. Jatkotutkimusmahdollisuuksia löytyisikin tutkimuskontekstin laajentamisesta.
Keywords: employer image, recruitment activities, personal experience, recruitment communication, instrumental-symbolic framework